P II – 1–7 Spatio-temporal analysis of the relationship between meteorological factors and hand-foot-mouth disease in beijing, china. (18th March 2018) - Tian, Lin; Clements, Archie; Pan, Xiaochuan
Abstract : Background/aim: Hand-foot-mouth disease (HFMD) is a common infectious disease in China and occurs mostly in infants and children. Beijing is a densely populated megacity, in which HFMD has been increasing in the last decade. The aim of this study was to quantify spatio-temporal characteristics of HFMD and the relationship between meteorological factors and HFMD incidence in Beijing, China. Methods: Daily counts of HFMD cases from January 2010 to December 2012 were obtained from the Beijing Centre for Disease Prevention and Control (CDC). Seasonal trend decomposition with Loess smoothing was used to explore seasonal patterns and temporal trends of HFMD. Bayesian spatiotemporal Poisson regression models were used to quantify spatiotemporal patterns of HFMD incidence and associations with meteorological factors. Results: There were 114, 777 HFMD cases reported to Beijing CDC from 1 January 2010 to 31 December 2012 and the raw incidence was 568.6 per 1 00 000 people. May to July was the peak period of HFMD incidence each year. Low-incidence townships were clustered in central, northeast and southwest regions of Beijing. Mean temperature, relative humidity, wind velocity and sunshine hours were all positively associated with HFMD. The effect of wind velocity was significant with a RR of 3.30 (95% CI: 2.37 to 4.60) per metre per second increase, as was sunshine hours with a RR of 1.20 (95% CI: 1.02 to 1.40) per one hour increase. Conclusion: The distribution of HFMD in Beijing was spatiotemporally heterogeneous, and was associated with meteorological factors. Meteorological monitoring could be incorporated into prediction and surveillance of HFMD in Beijing.